Microwave-assisted synthesis and evaluation of type 1 collagen–apatite composites for dental tissue regeneration. (July 2018) - Ilyas, Kanwal; Qureshi, Saba W; Afzal, Sadia; Gul, Roquyya; Yar, Muhammad; Kaleem, Muhammad; Khan, Abdul S
The aim was to develop an economical and biocompatible collagen-based bioactive composite for tooth regeneration. Acid-soluble collagen was extracted and purified from fish scales. The design was innovated to molecularly tailor the surface charge sites of the nano-apatite providing chemical bonds with the collagen matrix via microwave irradiation technique. The obtained collagen was identified by sodium dodecyl sulfate polyacrylamide gel electrophoresis analysis. The composites were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis/differential scanning calorimetry, and scanning electron microscopy. MC3T3-E1 cell lines were used to assess the biological effects of these materials by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetra zolium bromide (MTT) assay. Indirect contact test was performed by extracting representative elutes in cell culture media and sulforhodamine B analysis was performed. Chorioallantoic membrane assay was conducted to define the new vessels formation behavior. The purity of collagen extracts was determined and showed two α-chains, i.e. the characteristic of type I collagen. Fourier transform infrared spectroscopy showed the characteristic peaks for amide I, I, III, and phosphate for collagen and composites. Scanning electron microscopy images showed three-dimensional mesh of collagen/apatite nano-fibers. Nontoxic behavior of composites was observed and there were graded and dose-related effects on experimental compounds. The angiogenesis and vessels formation behavior were observed in bioactive collagen composite. The obtained composites have potential to be used for tooth structure regeneration.